Transformational leadership style and its relation to employees Integrity: findings from the study of government agency in Malaysia - Ahmad, Najihah; Mohamad Nor, Nur Baiti Ashiqin; Ghazali, Marni; Abd Razak, Shahidah; Moultone, Noorie Haryaniee (Universiti Teknologi MARA, Cawangan Melaka, 2019)
This aims to identify the level of employees integrity at the workplace; second to examine the relationship between transformational leadership dimensions with particular emphasized on (i) intellectual stimulation, (ii) individualized consideration, (iii) inspirational motivation and (iv) idealized influence with employees integrity; and lastly to determine the most influential dimension of the transformational leadership on employees integrity. Data was collected through a structured questionnaire from 136 respondents. The main analysis involved descriptive and inferential statistics in order to achieve the research objectives of the study respectively. The study findings revealed that the level of employees’ integrity is high at one of the government agency in Negeri Sembilan. Result also confirmed that transformational leadership dimensions were significantly related to employees’ integrity, it produces positive and moderate relationship with employees’ integrity. The study findings also indicated that the individualized consideration is the most significant predictor of employees’ integrity at the workplace.